2004
DOI: 10.1007/s10157-004-0286-y
|View full text |Cite
|
Sign up to set email alerts
|

Renal function at the time of renal biopsy as a predictor of prognosis in patients with primary AL-type amyloidosis

Abstract: Our study demonstrated that renal function at the time of biopsy and renal interstitial damage are the best predictors of survival in AL-type renal amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Cardiovascular disease and infection are two main causes of death. Oosawa [40] surveyed the clinical course of 21 patients with AL amyloidosis. Among them, 11 patients died after a mean period of 21.7 months after renal biopsy, whereas the other 10 who survived were followed up for 51.0 months.…”
Section: Clinical Diagnosis and Clinical Features Of Renal Amyloidosismentioning
confidence: 99%
“…Cardiovascular disease and infection are two main causes of death. Oosawa [40] surveyed the clinical course of 21 patients with AL amyloidosis. Among them, 11 patients died after a mean period of 21.7 months after renal biopsy, whereas the other 10 who survived were followed up for 51.0 months.…”
Section: Clinical Diagnosis and Clinical Features Of Renal Amyloidosismentioning
confidence: 99%
“…Several outcome studies have discussed the onset and progressive mechanisms of renal amyloidosis; however, detailed analyses of a large number of cases have not been undertaken (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…A large cohort of Chinese patients with renal amyloid light-chain amyloidosis study revealed that the degree of amyloid deposition in glomeruli was closely associated with proteinuria and renal function, higher vascular deposition of amyloid was associated with milder proteinuria, but not associated with renal insufficiency [10] . Osawa et al [19] reported that patients with renal amyloidosis with interstitial damage in the kidney had marked poorer prognosis than those without such damage. In addition, Yao et al [10] found that advanced glomerular deposition, interstitium amyloid deposition, inflammatory infiltration and existence of casts in tubules were all associated with renal insufficiency.…”
Section: Discussionmentioning
confidence: 98%